On sex and Discipline - Wiegman, Robyn (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
This essay examines the current debate between proponents of "queer theory" and "gay and lesbian studies" in order to understand the way each sets forth a political agenda for disciplinary and institutional social change. The author surmises that the utopian hope invested in each critical perspective evinces an affinity that is often overlooked in the way the debate is presented. Further, she argues that neither queer theory nor gay and lesbian studies currently pays adequate attention to the "local" politics of the institution, and she raises the possibility of a political horizon for institutional change which we might call "queering the academy."